2020
DOI: 10.46743/1540-580x/2020.1842
|View full text |Cite
|
Sign up to set email alerts
|

Student Experiences with Engagement in a Nursing and Physical Therapy Interprofessional Education Simulation

Abstract: Purpose: Interprofessional Education (IPE) incorporated into healthcare discipline instruction has been shown to be successful in improving the understanding perceptions of complimentary professions. The purpose of this mixed method study was to measure differences in perceptions of early Baccalaureate of Science in Nursing (BSN) students and Doctor of Physical Therapy (DPT) with participation in a immersive interprofessional education experience. Method: Students completed a pre and posttest survey consisting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…These results were expected, as multiple studies involving sim-IPE with physical therapy students found an immediate increase in students' perceptions. [7][8][9][10][11][12][13][14][15][16][17] Researchers have found that sim-IPE promotes positive student reactions, increases student understanding of successful teamwork, and improves their knowledge regarding roles and responsibilities. 7-8910111213141516 17,26 The initial ISVS-21 scores prior to sim-1 compared to the final scores after sim-3 indicate an overall statistically significant improvement in students' perceptions, attitudes, and beliefs regarding collaboration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were expected, as multiple studies involving sim-IPE with physical therapy students found an immediate increase in students' perceptions. [7][8][9][10][11][12][13][14][15][16][17] Researchers have found that sim-IPE promotes positive student reactions, increases student understanding of successful teamwork, and improves their knowledge regarding roles and responsibilities. 7-8910111213141516 17,26 The initial ISVS-21 scores prior to sim-1 compared to the final scores after sim-3 indicate an overall statistically significant improvement in students' perceptions, attitudes, and beliefs regarding collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…30 Sim-IPE allows students to practice and develop clinical skills in a controlled and safe learning environment. 16 Moreover, the use of realistic, simulated patient cases in interprofessional teams enables students to enhance their clinical reasoning, problem-solving, and communication skills. This collaborative approach fosters their ability to work effectively as part of a team.…”
mentioning
confidence: 99%
“…The MD students in turn learned about the expertise and roles of the PT students as it related to safety and safe patient handling [13]. Koplow et al reported that IPE experiences inclusive of RN and PT students showed increased knowledge about each other's scope of practice and the recognition of the value of teamwork [14]. Finally, a recent study by Sytsma et al was designed to assess readiness for interprofessional learning amongst second-year PT and fourthyear MD students before and after a four-hour IPE workshop [15].…”
Section: Review Of the Literaturementioning
confidence: 99%